N-ethyl-N-Nitrosourea (ENU) induced mutations within the klotho gene lead to ectopic calcification and reduced lifespan in mouse models - Esapa, C; Hannan, F; Babinsky, V; Potter, P; Thomas, G; Croucher, P; Brown, M; Brown, S; Cox, R; Thakker, R (Public Library of Science, 2015)
Ectopic calcification (EC), which is the pathological deposition of calcium and phosphate in extra-skeletal tissues, may be associated with hypercalcaemic and hyperphosphataemic disorders, or it may occur in the absence of metabolic abnormalities. In addition, EC may be inherited as part of several monogenic disorders and studies of these have provided valuable insights into the metabolic pathways regulating mineral metabolism. For example, studies of tumoural calcinosis, a disorder characterised by hyperphosphataemia and progressive EC, have revealed mutations of fibroblast growth factor 23 (FGF23), polypeptide N-acetyl galactosaminyltransferase 3 (GALNT3) and klotho (KL), which are all part of a phosphate-regulating pathway. However, such studies in humans are limited by the lack of available large families with EC, and to facilitate such studies we assessed the progeny of mice treated with the chemical mutagen N-ethyl-N-nitrosourea (ENU) for EC. This identified two mutants with autosomal recessive forms of EC, and reduced lifespan, designated Ecalc1 and Ecalc2. Genetic mapping localized the Ecalc1 and Ecalc2 loci to a 11.0 Mb region on chromosome 5 that contained the klotho gene (Kl), and DNA sequence analysis identified nonsense (Gln203Stop) and missense (Ile604Asn) Kl mutations in Ecalc1 and Ecalc2 mice, respectively. The Gln203Stop mutation, located in KL1 domain, was severely hypomorphic and led to a 17-fold reduction of renal Kl expression. The Ile604Asn mutation, located in KL2 domain, was predicted to impair klotho protein stability and in vitro expression studies in COS-7 cells revealed endoplasmic reticulum retention of the Ile604Asn mutant. Further phenotype studies undertaken in Ecalc1 (kl203X/203X) mice demonstrated elevations in plasma concentrations of phosphate, FGF23 and 1,25-dihydroxyvitamin D. Thus, two allelic variants of Kl that develop EC and represent mouse models for tumoural calcinosis have been established.